P02.01 Systematic review and meta-analysis of randomised control trials of interactive digital interventions for sexual health promotion. (13th September 2015) - Wayal, S; Bailey, JV; Murray, E; Rait, G; Morris, RW; Peacock, R; Nazareth, I
Abstract : Background: Sexual ill-health is a global concern. Digital technology offers enormous potential for health promotion. This systematic review assessed effectiveness of interactive digital interventions (IDI) for sexual health promotion. Methods: IDI are interactive programmes providing information, decision support, behaviour-change support and/or emotional support. We searched 40 electronic databases for randomised controlled trials (RCT) of IDI for sexual health promotion. Cochrane Collaboration methods were used to determine the effectiveness of IDI vs. minimal interventions (e.g. waiting list) (comparison1); face-to-face interventions (comparison 2); and different designs of IDI (comparison 3). Separate meta-analyses were conducted for comparisons 1, 2, and 3, by type of outcome (knowledge, self-efficacy, intention, sexual behaviour and biological outcomes). Results were pooled using a random effects model to calculate standardised mean differences (SMDs) and odds ratios (ORs). Subgroup analyses tested the following pre-specified factors: age, risk grouping, and settings (online, healthcare, educational). Results: We identified 34 RCTs (10, 758 participants). Comparison 1: IDI had beneficial effect on knowledge (SMD 0.43, 95% CI 0.14 to 0.71); safer sex self-efficacy (SMD 0.11, 95% CI 0.03 to 0.18) and intention (SMD 0.13, 95% CI 0.05 to 0.22). There was no effect on sexual behaviour (OR 1.15, 95% CI 0.97 to 1.36) or biological outcomes (OR 0.81, 95% CI 0.56 to 1.16). Comparison 2: IDI improved knowledge (SMD 0.36, 95% CI 0.1 to 0.58), and intention (SMD 0.46, 95% CI 0.06 to 0.85), but not self-efficacy (SMD 0.38, 95% CI 0.01 to 0.77). Comparison 3: Tailoring showed a beneficial effect on sexual behaviour (OR 2.64, 95% CI 1.45 to 4.80). No subgroup differences were noted. No data were available for cost-effectiveness. Conclusions: IDIs can effectively enhance knowledge, self-efficacy, intention, and tailored IDIs can improve sexual behaviour. Further evidence is needed to understand how to translate these positive effects of IDIs into improved sexual health, and how IDIs work. Disclosure of interest: Nothing to Declare.